Electron-donor doping enhanced Li storage in electride Ca2N monolayer: a first-principles study. (31st July 2018) - Wang, Hewen; Wu, Musheng; Tian, Zhengfang; Liu, Gang; Xu, Bo; Yang, Shengyuan A; Ouyang, Chuying
Abstract: It was reported by Hu et al (2015 ACS Appl. Mater. Interfaces 7 24016) that Li adsorption on the Ca2 N monolayer is energetically unfavorable, although it was found to be a good candidate for Na storage. In this paper, from first-principles calculations, it is shown that compressive stain can greatly enhance the interactions between Li adsorbate and the Ca2 N host, which is beneficial to prevent Li from clustering on the surface and thus Li storage becomes possible. Charge distribution analysis further shows that the enhanced Li-adsorption is a result of the increased surface charge density and the more confined charge distribution under compressive strain. Inspired by this observation, several electron-donor-doped Ca2 N materials are considered as anode materials for Li-ion batteries. Results show that the O and F doped Ca2 N have the best performance, with predicted Li storage capacity reaching about 567.9 and 565.9 mAh g −1 for O and F doped cases, respectively. It is also demonstrated that electron-donor doping does not change the metallic electronic structures and the low Li-ion migration energy barriers on the surface of the Ca2 N monolayer, and thus the rate performance of the doped Ca2 N can be as good as the undoped case. Our study offers a deep understanding of the Li interactions with 2D materials and provides an approach of material modification to 2D electrides for battery applications.